Fenologia da castanheira-do-Brasil (Bertholletia excelsa Humb. & Bonpl., Lecythidaceae) no sul do estado de Roraima - Tonini, Helio (2015)
This work was carried out in order to study the phenological pattern of brasil-nut trees in natural forest located in the south of Roraima state, in order to relate the frequency of occurrence of phenophases with rainfall. For the phenological survey 20 adult trees (DBH > 50 cm) were selected in a permanent sample plot of 9 ha. The phenological observations occurred fortnightly from February 2006 to February 2009, when data were collected on the presence or absence of events of fl owering, fruiting, leaf fl ushing and leaf fall for each tree. The Index of population synchrony was used for estimating the synchrony of phenological events. The fl owering of brasil-nut proved to be regular, annual, long and synchronous and was correlated with the reduction of rainfall. The fruiting was regular and synchronous, and dispersal was correlated with rainfall reduction. The phenological pattern of leaf fl ushing tended to vary yearly, being around the continual one in 2007 and bimodal in 2006 and 2008. It was noticed a higher proportion of trees falling leaves between August and October which characterizes a period of transition between the dry and the rainy time with sensitive reduction of rainfall.